HINAAN PUBLIK SEBAGAI ALASAN MERINGANKAN PIDANA DALAM PERKARA TINDAK PIDANA KORUPSI(STUDI PUTUSAN NOMOR 29/PID. SUS-TPK/2021/PN. JKT. PST) - Azzahra Dhea Safitri (2023)
The phenomenon of corruption that occurs in Indonesia has always been a timeless discussion. One of the efforts to eradicate corruption is to strengthen criminal sanctions imposed on perpetrators. However, in making a decision, the judge must formulate aggravating and mitigating circumstances. One of the reasons for mitigating the decision No. 29/PID. SUS-TPK/2021/PN. JKT. PST namely, the Defendant has suffered enough to be reviled, cursed at, humiliated by the public. The method used in this study uses normative juridical law research methods which are carried out by examining literature or secondary data with three approaches, namely the statutory approach, the conceptual approach, and the case approach. ). The results of this study show that the Judge in imposing Decision No.29/Pid-Sus/TPK/2021/PN Jkt. Pst. did not fulfill the principle of justice for the community because the judge did not accommodate the elements of the loss suffered by the community and the public's disappointed response to the perpetrators of the criminal act of corruption was instead used as an excuse to reduce the victim's sentence. In addition, the use of public insults as a mitigating reason for the defendant can trigger an imbalance in previous cases. Public condemnation should have given a warning to the panel of judges in considering the aggravating circumstances of the defendant. This is because the community feels aggrieved by the defendant's behavior.